2019
DOI: 10.1016/j.pmedr.2019.100870
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace, physical activity, and BMI in children from two cities in northern Mexico

Abstract: Numerous previous studies have reported positive associations between exposure to greenspace and children's physical activity, but in high-income countries only. Prior studies have also examined greenspace and obesity in children, but these have yielded inconsistent results and focused mostly on older children. The purpose of this study was to assess associations between time children spent in greenspace as the primary exposure and our outcomes of interest, including 1) minutes of physical activity, and 2) bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 74 publications
0
43
0
1
Order By: Relevance
“…We also found seven studies, including two cohort studies 8,31 and five cross‐sectional studies, 28,45,48,61,63 that focused on associations between NDVI and continuous BMI. Six of them 8,28,45,48,61,63 reported statistically significant associations between greater NDVI levels and lower BMI (i.e., estimated β values ranged from −0.18 to −0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found seven studies, including two cohort studies 8,31 and five cross‐sectional studies, 28,45,48,61,63 that focused on associations between NDVI and continuous BMI. Six of them 8,28,45,48,61,63 reported statistically significant associations between greater NDVI levels and lower BMI (i.e., estimated β values ranged from −0.18 to −0.05).…”
Section: Resultsmentioning
confidence: 99%
“…For example, James et al 16 concluded a lower risk of obesity associated with more greenspace, whereas Schulz et al 15 reported no association. Further, these reviews included articles published before 2016 and so could not incorporate several more recent high‐quality articles on this topic 9,10,28–48 …”
Section: Introductionmentioning
confidence: 99%
“…Green space accessibility has also been shown to have an inverse association with cardiovascular disease [ 11 ] and stress [ 12 ], while enhancing general health [ 13 ], mental health [ 14 ], and overall well-being [ 2 ]. Several studies have examined whether more green space exposure—including exposure to a higher density of green space [ 15 , 16 ], better proximity and accessibility [ 15 , 17 ], and a higher proportion of street trees [ 18 ]—has been associated with lower obesity rates, which is a key risk factor for several major chronic diseases; however, the literature overall on green space and obesity is equivocal [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Markevych et al [ 21 ] claimed two types of measurements for the pathway between green space and physical activity encouragement: (1) perceptual (i.e., time spent in green space, access and attractiveness, and safety), and (2) spatial (i.e., greenness, distance, and other qualities). Several studies using spatial measurements have shown that the amount of neighborhood greenness [ 1 , 20 , 22 ] and natural environments [ 15 ] are positively associated with increased physical activity levels among children and adults. In addition to the amount of green space, accessibility to green space is also associated with increases in walking and cycling [ 23 ] and moderate-to-vigorous physical activity (MVPA) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that time spent outdoors is positively related to reduced sedentary time and moderate and strenuous exercise in adults [ 19 , 20 , 21 , 22 , 23 ]. Harada et al showed that time spent outdoors was significantly and positively associated with physical activity measured as daily steps among 192 older adults, and suggested the health benefits of time spent outdoors were primarily mediated by physical activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%